Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $K$ be a field with non-zero elements $a,b,c \in K$ and let $(. , .)$ be the Hilbert symbol.

Let $(a,-c)=(-1,ac)$ and $(b,-c)=(-1,bc)$.

How to show that $(-ab,-c)=(-1,-abc)$ ?

share|cite|improve this question
I've computed: $(-ab,-c)=(-c,a)(-c,-b)=(-1,ac)(-c,-b)=(-1,ac)(-c,b)(-c,-1)=(-1,ac)(-1,bc)(-1,-c‌​)=(-1,-acbcc)$. But where is a mistake? – David75 Dec 2 '12 at 21:28
There is no mistake. Recall the definition of Hilbert symbol: $(-1, c^2) = 1$. – user27126 Dec 2 '12 at 21:29
Thanks! It's clear now :-) – David75 Dec 2 '12 at 21:33

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Browse other questions tagged or ask your own question.